2016
DOI: 10.5688/ajpe80223
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Emergency Preparedness Modules in Introductory Pharmacy Practice Experiences

Abstract: Objective. To determine the impact of emergency preparedness simulations in mass triage and mass dispensing on student pharmacist performance and perceived competency when assuming pharmacist roles in disaster situations. Design. Second-year student pharmacists (144) completed two 3-hour simulations focusing on mass triage and mass dispensing. The mass triage simulation consisted of virtual and live victims to be triaged and assigned a transport order. In the mass dispensing simulation, students assumed patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Elements of public health practice such as inclusion of social determinants of health (Hager et al, 2019) Walsh et al, 2012;Hannings et al, 2016;International Pharmaceutical Federation, 2016;Kim et al, 2017), community-based services or engagement (n=5) (Haddad et al, 2012;DiVall et al, 2013;Fritsch et al, 2016;Johnson & Traynor, 2018;, global health (n=4) (Benzian et al, 2015;Jogerst et al, 2015 All services and functions of public health (Lomazzi, 2016) were represented, with health promotion the most common, being discussed in 37 of the 58 papers. The public health functions of capacity (n=11) and governance (n=13) were least represented.…”
Section: Topics Of Included Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…Elements of public health practice such as inclusion of social determinants of health (Hager et al, 2019) Walsh et al, 2012;Hannings et al, 2016;International Pharmaceutical Federation, 2016;Kim et al, 2017), community-based services or engagement (n=5) (Haddad et al, 2012;DiVall et al, 2013;Fritsch et al, 2016;Johnson & Traynor, 2018;, global health (n=4) (Benzian et al, 2015;Jogerst et al, 2015 All services and functions of public health (Lomazzi, 2016) were represented, with health promotion the most common, being discussed in 37 of the 58 papers. The public health functions of capacity (n=11) and governance (n=13) were least represented.…”
Section: Topics Of Included Papersmentioning
confidence: 99%
“…Use of strategies that show awareness of and respect for individuals and patient-centredness Recognition of own beliefs and behaviours Pfleger et al,(2008), Strand & Miller,(2014), Rutland & Smith,(2010), Fritsch et al,(2016, NHS,(2014), NICE,(2018), Healthy People,(2020), Maffeo et al, (2009), Devraj et al,(2010, Hannings et al,(2016), Janke et al,(2013), , Teng et al,(2016), Johnson & Traynor,(2018), Holden & Evans,(2019) Rutland & Smith,(2010), Fritsch et al,(2016), NHS,(2014), Healthy People,(2020), Janke et al,(2013), Medicines management…”
Section: Cultural Competencymentioning
confidence: 99%
“…Educational training in disaster preparedness has typically engaged healthcare students in medicine, nursing, and pharmacy (8,9). Multiple studies have shown that interprofessional disaster simulation scenarios can be effective tools to build confidence and readiness in disaster response (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 91.4% of medical students stated that they would appreciate the introduction of an optional module that would educate them on disaster medicine and 94.1% indicated that a knowledge of disaster medicine would be helpful in their future career [3]. Although pharmacists can make many contributions in a variety of emergencies and during a disaster response, their specific role is not well defined [4,5]. Indeed, chemical, biological, radiological, and nuclear (CBRN) risks, including nerve agents, vesicants, radionucleotides, anthrax, and ricin poisoning, could require hospital pharmacies to provide antidotes, antibiotics, antitoxins, and other pharmaceuticals in large amounts [5].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, chemical, biological, radiological, and nuclear (CBRN) risks, including nerve agents, vesicants, radionucleotides, anthrax, and ricin poisoning, could require hospital pharmacies to provide antidotes, antibiotics, antitoxins, and other pharmaceuticals in large amounts [5]. Moreover, with the increasing risk of mass casualty events, pharmacists may also function as first-line responders in case of man-made disasters or as second-line responders caring for victims in health-system or community settings [4]. Therefore, it is crucial to equip pharmacists with the skills and knowledge necessary for any of these eventualities.…”
Section: Introductionmentioning
confidence: 99%